Atherothrombosis and Thromboembolism: Position Paper from the Second Maastricht Consensus Conference on Thrombosis - Spronk, H. M. H.; Padro, T.; Siland, J. E.; Prochaska, J. H.; Winters, J.; van der Wal, A. C.; Posthuma, J. J.; Lowe, G.; d'Alessandro, E.; Wenzel, P.; Coenen, D. M.; Reitsma, P. H.; Ruf, W.; van Gorp, R. H.; Koenen, R. R.; Vajen, T.; Alshaikh, N. A.; Wolberg, A. S.; Macrae, F. L.; Asquith, N.; Heemskerk, J.; Heinzmann, A.; Moorlag, M.; Mackman, N.; van der Meijden, P.; Meijers, J. C. M.; Heestermans, M.; Renné, T.; Dólleman, S.; Chayouâ, W.; Ariëns, R. A. S.; Baaten, C. C.; Nagy, M.; Kuliopulos, A.; Posma, J. J.; Harrison, P.; Vries, M. J.; Crijns, H. J. G. M.; Dudink, E. A. M. P.; Buller, H. R.; Henskens, Y. M.C.; Själander, A.; Zwaveling, S.; Erküner, O.; Eikelboom, J. W.; Gulpen, A.; Peeters, F. E. C. M.; Douxfils, J.; Olie, R. H.; Baglin, T.; Leader, A.; Schotten, U.; Scaf, B.; van Beusekom, H. M. M.; Mosnier, L. O.; van der Vorm, L.; Declerck, P.; Visser, M.; Dippel, D. W. J.; Strijbis, V. J.; Pertiwi, K.; ten Cate-Hoek, A. J.; ten Cate, H. (Thrombosis and Haemostasis, 2018)
Atherothrombosis is a leading cause of cardiovascular mortality and long-term morbidity. Platelets and coagulation proteases, interacting with circulating cells and in different vascular beds, modify several complex pathologies including atherosclerosis. In the second Maastricht Consensus Conference on Thrombosis, this theme was addressed by diverse scientists from bench to bedside. All presentations were discussed with audience members and the results of these discussions were incorporated in the final document that presents a state-of-the-art reflection of expert opinions and consensus recommendations regarding the following five topics: 1. Risk factors, biomarkers and plaque instability: In atherothrombosis research, more focus on the contribution of specific risk factors like ectopic fat needs to be considered; definitions of atherothrombosis are important distinguishing different phases of disease, including plaque (in)stability; proteomic and metabolomics data are to be added to genetic information. 2. Circulating cells including platelets and atherothrombosis: Mechanisms of leukocyte and macrophage plasticity, migration, and transformation in murine atherosclerosis need to be considered; disease mechanism-based biomarkers need to be identified; experimental systems are needed that incorporate whole-blood flow to understand how red blood cells influence thrombus formation and stability; knowledge on platelet heterogeneity and priming conditions needs to be translated toward the in vivo situation. 3. Coagulation proteases, fibrin(ogen) and thrombus formation: The role of factor (F) XI in thrombosis including the lower margins of this factor related to safe and effective antithrombotic therapy needs to be established; FXI is a key regulator in linking platelets, thrombin generation, and inflammatory mechanisms in a renin–angiotensin dependent manner; however, the impact on thrombin-dependent PAR signaling needs further study; the fundamental mechanisms in FXIII biology and biochemistry and its impact on thrombus biophysical characteristics need to be explored; the interactions of red cells and fibrin formation and its consequences for thrombus formation and lysis need to be addressed. Platelet–fibrin interactions are pivotal determinants of clot formation and stability with potential therapeutic consequences. 4. Preventive and acute treatment of atherothrombosis and arterial embolism; novel ways and tailoring? The role of protease-activated receptor (PAR)-4 vis à vis PAR-1 as target for antithrombotic therapy merits study; ongoing trials on platelet function test-based antiplatelet therapy adjustment support development of practically feasible tests; risk scores for patients with atrial fibrillation need refinement, taking new biomarkers including coagulation into account; risk scores that consider organ system differences in bleeding may have added value; all forms of oral anticoagulant treatment require better organization, including education and emergency access; laboratory testing still needs rapidly available sensitive tests with short turnaround time. 5. Pleiotropy of coagulation proteases, thrombus resolution and ischaemia–reperfusion: Biobanks specifically for thrombus storage and analysis are needed; further studies on novel modified activated protein C–based agents are required including its cytoprotective properties; new avenues for optimizing treatment of patients with ischaemic stroke are needed, also including novel agents that modify fibrinolytic activity (aimed at plasminogen activator inhibitor-1 and thrombin activatable fibrinolysis inhibitor.
Keywords: atherothrombosis; arterial thrombosis; coagulation; platelets; antiplatelet therapy; anticoagulants; atherosclerosis; ischaemic stroke; atrial fibrillation; myocardial infarction